The Role of Credit Financing for Capital Investments of The Real Economy Enterprises - Alexander M. Konorev; Maxim V. Barsukov; Lyudmila M. Osinevich (Communications of International Proceedings, 2021)
The transition from vertically distributed financial resources to horizontally distributed ones among market participants led to the shortage of the government support to the real economy enterprises for their investment activities. The shortage of equity also does not promote the modernization of production facilities. At the same time, the development of favorable conditions for stimulation of economic growth is one of priorities for the government. The implementation of such conditions in many respects depends on the involvement of the banking sector into financing of the investments into fixed capital realized by the enterprises of the real sector of economy. This article also observes interdependence of economic growth and the financing of investments into fixed capital. The research revealed strong correlation between the volume of investment into fixed capital and GDP growth, trends and patterns of financing of investments into fixed capital under current economic circumstance were defined. The structure of sources of the investment financing was analyzed and the respective conclusion on insufficiency of banking credit financing of the investment into fixed capital of the enterprises of the real sector was proven. As result the research provides suggestions on increasing of the banking sector role and its involvement in the investment financing in fixed capital of the non-financial organizations.
Keywords: investments; fixed capital; economic growth; credit sources; financing